Dysfunction of RNA/RNA-Binding Proteins in ALS Astrocytes and Microglia - Simona Rossi (MDPI AG, 2021)
Amyotrophic Lateral Sclerosis is a neurological disease that primarily affects motor neurons in the cortex, brainstem, and spinal cord. The process that leads to motor neuron degeneration is strongly influenced by non-motor neuronal events that occur in a variety of cell types. Among these, neuroinflammatory processes mediated by activated astrocytes and microglia play a relevant role. In recent years, it has become clear that dysregulation of essential steps of RNA metabolism, as a consequence of alterations in RNA-binding proteins (RBPs), is a central event in the degeneration of motor neurons. Yet, a causal link between dysfunctional RNA metabolism and the neuroinflammatory processes mediated by astrocytes and microglia in ALS has been poorly defined. In this review, we will discuss the available evidence showing that RBPs and associated RNA processing are affected in ALS astrocytes and microglia, and the possible mechanisms involved in these events.